Galvanochemical formation of a multicomponent alloy based on cobalt and refractory metals - Hapon, Yu. K.; Nenastina, T. O.; Sakhnenko, N. D.; Ved, M. V. (Kyiv National University of Technologies and Design, 2016)
Effects of major parameters of electrolysis on the composition and morphology of the cobalt-molybdenum-tungsten alloy from citrate- pyrophosphate and citrate-ammonium electrolytes have been analysed. It has been shown that the content of component metals in the Co-W-Mo alloy depends on the nature and composition of the electrolyte solution. The influence of electrolysis conditions and regime on the structure and morphology of cobalt alloys with refractory metals has been established. The elemental composition and morphology of the triple cobalt - molybdenum - tungsten coatings have been determined with a scanning electron microscope.

Проаналізовано вплив основних параметрів електролізу на склад та морфологію сплаву кобальт-молібден-вольфрам отриманого з цитратно-дифосфатного та цитратно-амоніачного електролітів. За допомогою сканівного електронного мікроскопу досліджено склад і морфологію потрійних покриттів. Було показано, що вміст компонентів в сплаві Со-W-Мо залежить від природи ліганда і співвідношення концентрацій сплавотвірних металів. Встановлено вплив густини струму, а також часу імпульсу та паузи на структуру і морфологію покриттів.
Гальванохімічне формування багатокомпонентного сплаву на основі кобальта та тугоплавких металів
Keywords: electrolysis; alloy Co-W-Mo; electrolyte solution; refractory metals; електроліз; електроліт; сплав Со-W-Мо; сплавотвірні метали